AKT isoforms modulate Th1‐like Treg generation and function in human autoimmune disease. (5th August 2019) - Kitz, Alexandra; de Marcken, Marine; Gautron, Anne‐Sophie; Mitrovic, Mitja; Hafler, David A; Dominguez‐Villar, Margarita
Abstract :